Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.11611/yead.327329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Empowerment on Work Engagement: A Research on Health Sector Employees

Abstract: Akademisyen ve uygulayıcıların psikolojik güçlendirme ve çalışmaya tutkunluk konularına olan ilgisi son yıllarda önemli ölçüde artmıştır. Bununla birlikte, birbirinden bağımsız olarak ortaya çıkan bu kavramların boyutlarının nasıl ilişkili oldukları konusunda yapılan çalışma sayısı oldukça yetersizdir. Bu çalışmanın amacı psikolojik güçlendirmenin boyutlarının çalışmaya tutkunluğun boyutları üzerindeki etkisini analiz etmektir. Çalışma kapsamındaki veriler Bursa'da bulunan sağlık kurumlardaki 146 katılımcıdan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…This is in line with self-determination theory (Ryan and Deci 2001), therefore, when expatriate employees fear losing their job, they increase their engagement at work and share more knowledge. Similarly, Stander and Rothmann (2010) and Serenko and Bontis (2016) note that external pressures caused by job insecurity can change employees' behavior, leading them to tend to display more positive behaviors to secure their job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with self-determination theory (Ryan and Deci 2001), therefore, when expatriate employees fear losing their job, they increase their engagement at work and share more knowledge. Similarly, Stander and Rothmann (2010) and Serenko and Bontis (2016) note that external pressures caused by job insecurity can change employees' behavior, leading them to tend to display more positive behaviors to secure their job.…”
Section: Discussionmentioning
confidence: 99%
“…Cuyper and De Witte ( 2005), De Cuyper et al ( 2008) and Stander and Rothmann (2010) found job insecurity to be negatively related to employees' engagement. On the basis of the foregoing, this paper proposes the following hypothesis:…”
Section: Links Between Job Insecurity Work Engagement and Burnoutmentioning
confidence: 98%
“…Literatür incelendiğinde bezdirinin zamanla işgörenlerin sadakatlerinde azalmaya neden olduğu, işgörende alternatif iş arama niyeti oluşturduğu, bunların sonucu olarakta örgütlerde işgören devir hızını arttırdığı, kişisel olarak çalışanın motivasyon, verimlilik, iş tatminlerini ve örgütsel bağlılık gibi pozitif moral değerlerinde azalma meydana geldiği (Einarsen ve diğ., 1994: 381;Niedl, 1996: 241;Vartia, 1996: 203;Zapf ve diğ.,1996: 215), işgörenleri örgütten soğuttuğu ve ayrıca işgörenin örgütsel bağlılığını negatif yönde etkilediği (Demirel, 2008;Ergener, 2008: 69;Özler ve diğ., 2008: 55;Tunçel, 2009: 190;Yaman, 2009: 133) sonuçlarına ulaşılmaktadır. Araştırmamızın sonuçlarının gerek yurt içi gerekse yurt dışındaki literatürle tutarlı olduğu söylenebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified